PREVENTING VIOLENCE CRIMES (KIDNAPPING, ARMED ROBBERY, BRIGANDAGE OR COMMUNITY MASSACRE) WITH DRONES: AN EFFECTIVE ALTERNATIVE TO VEHICULAR PATROLS IN NIGERIA - GABRIEL SALIFU; DANIEL OLASUNKANMI OLADAPO (International Studies Journal)
The family, society and morality, to borrow the most ecological terminology, have become “endangered species”. Studies on parenting have focused on psychological, sociological, gender roles and traditional perspectives. However much has not been said about the dimension of parents as home builders a sine-qua-non for national development from Christian standpoint. Data for this work were collected through oral interview and consultation of scholarly journals and textbooks. In the 21st century, the families off springs are endangered with multiple social vices that range from internet fraud (yahoo yahoo), kidnapping, lesbianism, drug abuse, homosexuality, bestiality, incest, ritual killing and others. Some of these issues if not all are gaily celebrated in most of our churches and shrines as they are being aided in all front. Parents have self-imposed and natural duty to train up their children without treating it as a second class duty, that there is a link between effective parenting, morality and national development. Findings from this work has indicated that responsible citizenry, reduction in crime rate, healthy nation and preservation of cultural values which are germane to national development are products of responsible parenting. Also discovered, are the salient roles of women (responsibility in children upbringing, character study, mirror of the family and caretakers) which are imperative for effective parenting, tutelage and admonition of children in families. The work recommends.